Concentration Ratio of Gelatine and Polyvinylpyrrolidone as Binder on Physical Properties of Red (Zingiber officinale Rosc.) Extract Lozenges - Gusmayadi, Inding; Priyanto, Priyanto (LPPM STIKes Muhammadiyah Ciamis, 2024)
Lozenges have the requisite tablets hardness value 7-14 Kgf, to achieve it using gelatine as suitable binder. Gelatine makes granules with bad flow time. PVP make granules with better flow time but it takes large quantity to reach hardness lozenges. This study aims at determining the effect of concentration ratio of gelatine and PVP as binder on the physical properties of red-ginger extract lozenges. Lozenges made using wet granulation method in variation of the concentration of gelatine and PVP as follows 1:1, 1:2, 1:3, 1:4 and 1:5. Hardness test results obtained from the formula 1 to formula 5 are 9, 14, 16, 13 and 12 Kgf and friability test results are 0,4%, 0,7%, 0,2%, 0,3% and 0,6%. The combination of gelatine and PVP as binder can provide meaningful difference in hardness and friability tablet.